An Exploration of Students' Sociometric Status Based on Their Behaviors in the EFL Speaking Class - Marlia Marlia; Ima Asmita Marwan (Faculty of Education and Teacher Training of UIN Palopo, 2025)
Social interaction among peers became fundamental to be scrutinized, especially in the secondary educational context, which determined the atmosphere of classroom acceptance and the positive relationship. Furthermore, sociometric status refers to the measurement to classify an individual's relationship among peers or groups of friends and the measurement indicating whether the individual is liked or disliked by their peers. This study aimed to explore students' sociometric status toward peer relationships concerning students' behaviors based on the categorization of sociometric status, especially in the EFL speaking class. Thirty-three students in the eleventh grade of the social science class were purposively selected from secondary education to participate in this study. The data were collected through an observation checklist to get students' behaviors. A rating-scale measure was distributed to the students to determine five sociometric status categories among peers. Based on the five categorization of sociometric status among students they were popular, controversial, rejected, neglected, and average have proved that the majority of the students displayed positive behaviors which categorized into highly-positive behaviors (providing assistance, providing direction, and medium-positive behaviors (providing jokes) and only few students displayed negative behaviors were categorized into highly negative-behaviors (inappropriate behaviors, angry shouting, hitting and medium-negative behaviors (noncompliance, disapproval) in the EFL speaking classroom. In conclusion, all five sociometric statuses reflected positive and negative behaviors during the learning process in the EFL classroom.